2021
DOI: 10.1186/s12937-020-00661-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and chronic kidney disease risk: a systematic review and updated meta-analysis of observational studies

Abstract: Background A number of studies have reported the association between dietary patterns and the risk of chronic kidney disease (CKD), however a consistent perspective hasn’t been established to date. Herein, we conducted this systematic review and meta-analysis of observational studies to assess the association between dietary patterns and CKD. Methods MEDLINE, EBSCO and references from eligible studies were searched for relevant articles published u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
(102 reference statements)
0
17
0
Order By: Relevance
“…The Newcastle-Ottawa Scale ( 20 ) was used to identify the quality of included studies in the meta-analysis. This scale consisted of three main domains: selection of participants with maximum 4 stars, comparability of participants with maximum 2 stars, and assessment of outcome/exposure with maximum 3 stars.…”
Section: Methodsmentioning
confidence: 99%
“…The Newcastle-Ottawa Scale ( 20 ) was used to identify the quality of included studies in the meta-analysis. This scale consisted of three main domains: selection of participants with maximum 4 stars, comparability of participants with maximum 2 stars, and assessment of outcome/exposure with maximum 3 stars.…”
Section: Methodsmentioning
confidence: 99%
“…Two exploratory factor analyses that assessed food consumption and derived a posteriori food patterns in a CKD population placed fish in the pattern described as “mixed” [ 72 ] or “unhealthy” [ 73 ], along with red meat and poultry, probably because of these foods’ high protein content. A more recent systematic review and meta-analysis of 17 observational studies involving 149,958 participants that assessed the association between common dietary patterns and CKD, however, found that a healthy dietary pattern associated with a lower risk of CKD was characterized by a high intake of vegetables, fruits, fish, low-fat milk, and whole grains [ 74 ].…”
Section: Dietary Approach To Dyslipidemia In Ckd Patientsmentioning
confidence: 99%
“…Likewise, a recent systematic review and meta- analysis published in 2022 by Zhang et al higher intakes of processed meats, processed fish and grains were significantly associated with the increased risk of glioma ( 8 ). However, because of the complexity nature of dietary constituents and the potential interactions between foods and nutrients ( 15 ), these priori studies revealed the limited impact of diet on glioma. In this context, dietary pattern analyses, as new direction in nutritional epidemiology, have emerged to take the combined effects of foods and nutrients into account ( 16 ).…”
Section: Introductionmentioning
confidence: 99%